Automotive cabin vent: Comparison of RANS and LES approaches with analytical-empirical equations and their validation with experiments using Hot-Wire Anemometry. (1st April 2023) - Sip, Jan; Lizal, Frantisek; Pokorny, Jan; Elcner, Jakub; Jedelsky, Jan; Jicha, Miroslav
Abstract: The velocity field downstream of an automotive vent is one of the key parameters of passenger comfort. Two theoretical approaches (using analytical-empirical equations, and based on computational fluid dynamics) were applied to calculate the velocity of a jet emerging from a real rectangular benchmark ventilation outlet with adjustable blades. The computational simulations were performed by solving the Reynolds-averaged Navier–Stokes equations (RANS) with the realizable k-ε turbulence model and by Large Eddy Simulation (LES). The results were validated by experimental data acquired by constant temperature anemometry (CTA). The validation comprised a comparison of axial velocity decay, scalar velocity field, angles of jet inclination, and profiles of velocity and turbulence intensity. The study was performed for the isothermal free jet and attached jet, where surrounding walls simulated confinement in a car cabin. The analytical empirical equation by Rajaratnam can be successfully used also to determine the throw of the jet, which is favourable, especially in light of the fact that both computational methods were not very accurate in velocity decay predictions. Root mean square errors for the free jet, and attached jet (expressed for calculations made according to Rajaratnam, and by LES and RANS with respect to the experimentally measured values) were 0.50, 0.85, 0.87 m s −1, and 0.52, 0.30, 0.65 m s −1, respectively. The LES method was more accurate than RANS in predicting the velocity profiles. The average percentage error of LES, and RANS is 6.3%, and 17.4%, respectively however, the calculation time was almost 27 times higher for LES. Graphical abstract: Image 1 Highlights: The LES/RANS method is suitable for evaluating the flow field downstream of the automotive vent. Rajaratnam's equation provides the best accuracy of axial velocity decay. Both CFD methods (LES and RANS) provided good predictions of turbulence intensity.